Assessing Impacts of Climate Variations and Change on Different Time Scales - Korhonen, Natalia (Helsingin yliopisto, 2020)
Climate change refers to a change in the mean state of the climate that persists for an extended period, typically 30 years or longer. The natural inter-annual variability of climate refers to internal variation of the climate system in shorter time-scales. In this thesis I have studied the climate of the last glacial and its impact on human population sizes in Europe during the end of the last glaciation, the change in forest fire danger and strong winds in Europe under the on-going human-induced climate change, and the relationship between the stratospheric winds and the phase of the Arctic Oscillation in present climate. A regression model was developed to downscale low-resolution dynamical EMIC simulations to regional scale. The regression model was calibrated by gridded data of regional scale resolution observations of present day climate and simulations of glacial climate. The downscaled climate was used in estimating the size of human population in Europe during the end of the last glaciation, between 30,000 and 13,000 years ago. The simulated changes in human population size correlated significantly with an independent archeological data of changes in human population size. The change in the forest fire danger in Europe was investigated by ERA-Interim and ERA-40 reanalysis. The forest fire danger was found to have increased in Southern and Eastern Europe during the period 1980–2012, whilst no significant trend was found elsewhere in Europe. The projected changes in the geostrophic wind speeds under human-induced climate change in Northern Europe during the current century were explored from simulations of nine general circulation models. According to the simulations, the changes in mean and extreme wind speeds are going to be small; in parts of northwestern Russia and southern Baltic Sea the winds might increase by 2-4% and over the Norwegian Sea the winds might decrease by 2-8%. In this thesis the connection between the stratospheric winds and surface Arctic Oscillation was studied statistically. The ...